Peran Moderasi Toleransi Pelanggan terhadap Pengaruh Pengalaman Pelanggan Terhadap eWOM Negatif - Sanaji Sanaji (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
A customer's negative voice can be detrimental to the company when the negative voice is widespread in society. One factor that drives customers to speak negatively is the negative experience they receive when making a purchase. This study aims to confirm the moderating role of customer tolerance which is expected to reduce the effect of negative experiences on negative electronic word-of-mouth (eWOM). The model was tested using Partial Least Square – Structural Equation Modeling (PLS-SEM) from 209 samples. Data analysis found that negative experiences had a positive effect on negative eWOM. The results of the moderation analysis concluded that customer tolerance is a pure moderator in moderating negative customer experiences towards negative eWOM. Unlike the initial expectation, the results of the moderation test show that customer groups with low tolerance can reduce the effect of negative experiences on negative eWOM. Conversely, customers with a high tolerance increase the influence of adverse experiences on negative eWOM.